Using table tennis record form to explore 2018 World Tour Grand Finals men`s single player`s crucial technical and tactical - Sun, Y.; Chiu, H.-T. (Proceedings Book of The 16th ITTF Sports Science Congress Budapest (HUN), April 19th - 20th, 2019, 2020)
In table tennis competition, player`s on-the-spot response and coaches using different technical and tactical during the match are indispensable. The purpose of the study is to explore the technical and tactical performance and application of men's singles quarter-finals in 2018 World Tour Finals. The study used table tennis record form to record the match and analyse the data. The form record player's winning point, hitting technique and error position. The data through Excel to run statistical analysis and make hot zone to find out player perfect shot technique and error position. After statistical analysis and discussion, there are three conclusions. First, players of quarter-finals had high rate error on the position1 and position3. Second, the hitting technique of winning point mostly uses the backhand attack. Third, winning points are mostly hitting as slash direction. The results of data analysis enable the coach to communicate the tactics clearly and effectively to the player during the game. This analysis technology not only helps the player to improve their self-confidence and confront different opponent tactical changes but also the data can assist the player to strengthen their weaknesses technique during usual practice.